2007
DOI: 10.1021/es0622249
|View full text |Cite
|
Sign up to set email alerts
|

Unregulated Emissions from a Heavy-Duty Diesel Engine with Various Fuels and Emission Control Systems

Abstract: This study evaluated the effects of various combinations of fuels and emission control technologies on exhaust emissions from a heavy-duty diesel engine tested on an engine dynamometer. Ten fuels were studied in twenty four combinations of fuel and emission control technology configurations. Emission control systems evaluated were diesel oxidation catalyst (DOC), continuously regenerating diesel particulate filter (CRDPF), and the CRDPF coupled with an exhaust gas recirculation system (EGRT). The effects of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…The reductions in PAHs range from 80% to more than 99% relative to a 2000-technology engine. 19 All PAHs with more than four rings except fluoranthene and pyrene were below the detection limit. Table 8 reports a 92% reduction in nitroPAH compound emissions with the 2007-technology engines.…”
Section: Resultsmentioning
confidence: 94%
“…The reductions in PAHs range from 80% to more than 99% relative to a 2000-technology engine. 19 All PAHs with more than four rings except fluoranthene and pyrene were below the detection limit. Table 8 reports a 92% reduction in nitroPAH compound emissions with the 2007-technology engines.…”
Section: Resultsmentioning
confidence: 94%
“…17 Other studies have also reported similarly high EC and OC reductions across a range of engines, aftertreatment configurations, test cycles, and fuel sulfur content. 25,26,28,37,38 For example, Liu et al 28 observed >99% reductions for both EC and OC in their comprehensive study of emissions of more than 150 organic species from a 2007 engine representative of NTDE versus a 2004 non-retrofit engine (see Table 1 for engine specifications).…”
Section: Major Chemical Speciesmentioning
confidence: 99%
“…Tang et al reported that for all of the fuels studied the TC mass emissions were reduced by the DOC and the EC/OC ratio was increased due to more reduction of OC than EC emissions [18]. In this study, the variation of the OC/EC ratio after the DOC was not consistent and depended on operating conditions.…”
Section: Pm Sampling and Composition Analysismentioning
confidence: 54%